PENDIDIKAN GENDER DALAM PENGKAJIAN ISLAM - Da’watiz Zahroh, Chichi ‘Aisyatud (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2019)
Women's struggle demands equal rights with men known as gender equality Many Islamic religious doctrines are lame on gender because religious texts are understood textually. The issue of gender inequality stemming from Islamic religious doctrine can be overcome by using new methodologies in understanding religious texts that are considered gender deviations. Gender inequality is strengthened when men carry status as a protector of women while gentle women become protected, supported by limited tasks at home. The difference between the two is due to the main functions and tasks God imposes on each sex. Many theories have been advanced by the expert on the beginning of the concept of gender and the factors that preserve it in the future. Globalization that increasingly criticize women, make women require appreciation in the framework of modern civilization and contemporary human civilization. This mainstrem area is the concern of the world community. Gender is questioned about the existence of women in the global civilization, politics, education, and education of Islam. So the thinking of the figure is needed to find a middle issue is a matter of gender is the female feminist fighters namely Fatima Mernissi